2021
DOI: 10.13107/jocr.2021.v11.i02.2008
|View full text |Cite
|
Sign up to set email alerts
|

Limb Salvage Surgery in Fungating Giant Cell Tumors: A Report of Three Cases

Abstract: Introduction: The WHO defines giant cell tumor as a benign locally aggressive neoplasm with metastasizing capacity and aggressive behavior. Very rarely, these tumors are seen fungating, mostly when neglected. But when they do, the treatment option commonly conferred is amputation of the limb which is disabling and traumatizing. Case Report: We report three cases of fungating limb masses (proximal tibia, distal fibula, and distal radius) diagnosed with giant cell tumor histologically, undergoing limb saving sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The meshplasty is another technique that exploits the properties of a folded polypropylene mesh in determining intense fibrosis in surrounding tissue and providing adequate strength to stabilize the joint ( Fig. 4A ) ( 17 , 37 ). Prajapat et al describe the technique as easy, reproducible, and with minimal complications ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meshplasty is another technique that exploits the properties of a folded polypropylene mesh in determining intense fibrosis in surrounding tissue and providing adequate strength to stabilize the joint ( Fig. 4A ) ( 17 , 37 ). Prajapat et al describe the technique as easy, reproducible, and with minimal complications ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A summary of patients treated with resection of the distal fibula and reconstruction modalities such as arthrodesis, arthroplasty, and other reconstruction options is presented in Table 4 ( 17 , 18 , 22 , 31 , 37 , 44 , 64 , 65 , 66 , 68 , 69 ). Mansour and Ghanem ( 66 ) reported on a two-staged procedure described as a variant of the Masquelet technique ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GCTs of the distal fibula are a rare occurrence, as evident by the fact that there are only seven studies to date that report the occurrence of GCTs involving the distal fibula [4,[15][16][17][18][19][20]. These tumors are catastrophic and destroy the affected bone, thus affecting the mobility of the respective joint.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting case study published by Rangaswamy et al elaborates on a bleeding lesion at the lateral malleolus of the left leg that manifested as a recurrence of a GCT of the distal fibula that was treated by curettage a year before. The tumor was resected, and mesh and screws were used to stabilize the joint [18]. The Campanacci grading system has been utilized for the classification of GCT based on the radiographic appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Ten percent of cases are located at the distal radius [6]. It was reported that distal radius GCT could exhibit larger sites and be more aggressive than usual [5]. Tumor sites of ≥ 5 cm in diameter had a 3.893 times higher rate of recurrence [2].…”
Section: Discussionmentioning
confidence: 99%